Designing an artificial intelligence-powered video assistant referee system for team sports using computer vision - Maigul Zhekambayeva; Meruert Yerekesheva; Nurmambek Ramashov; Yermek Seidakhmetov; Bakhytzhan Kulambayev (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This paper investigates the efficacy of an AI-powered Video Assistant Referee (VAR) system in enhancing officiating accuracy, efficiency, and consistency in team sports. Employing a combination of artificial intelligence and computer vision, the system was tested in a local championship in Almaty, involving eight football teams. Through the analysis of decision-making accuracy, time efficiency, and consistency across officiating scenarios, the study employed chi-squared tests, paired t-tests, and Cohen's Kappa statistics to quantitatively assess improvements over traditional VAR systems. Results indicated that the AI-powered VAR system significantly increased the accuracy of decisions and reduced the decision-making time, thereby maintaining the fluidity of gameplay. Although the system also demonstrated enhanced consistency in officiating decisions, it highlighted areas needing further refinement to handle complex game situations effectively. The findings suggest that AI integration into sports officiating can substantially benefit the fairness and dynamics of team sports, provided that ongoing technological advancements continue to address current limitations. This study contributes to the growing body of knowledge on the intersection of technology and sports, offering a framework for future enhancements in digital officiating systems.